IMPLEMENTASI SISTEM MANAJEMEN PERSEDIAAN KAPORSATLAP BERBASIS WORDPRESS DENGAN METODE FIRST IN FIRST OUT (FIFO) - Restu Saka Kertanegara; Khairul Muslim (JURNAL DWIJA KUSUMA, 2026)
Kaporsatlap inventory management at Bekangdam III/Siliwangi plays a strategic role in supporting military operational readiness. However, inventory management is still conducted manually, which often leads to recording errors, delays in stock information, and inconsistent implementation of the First In First Out (FIFO) method. This study aims to implement a WordPress-based inventory management system integrated with the FIFO method to improve logistics management efficiency. The research employed a Research and Development (R&D) approach with descriptive and evaluative quantitative analysis. The research subjects consisted of ten warehouse personnel at managerial, supervisory, and operational levels. Data were collected through observation, interviews, Likert-scale questionnaires, and documentation. The results show that the implementation of a WordPress-based inventory system significantly improves inventory management efficiency. Stock search time decreased from 17.5 minutes to 2.5 minutes, recording errors dropped from four to 0.5 times per week, and FIFO compliance increased from 65% to 95%. In addition, correlation analysis indicates a strong positive relationship between system usage and logistics efficiency improvement (r = 0.74). These findings demonstrate that integrating the FIFO method with a WordPress-based information system can improve inventory accuracy, logistics distribution efficiency, and decision-making quality in military supply management.